PERCEPTIONS OF IRAQI IMMIGRANT EMPLOYMENT DISCRIMINATION IN THE METRO DETROIT AREA - Abel, Murad (PEOPLE: International Journal of Social Sciences, 2017)
Society is changing rapidly and the United States is a global community in transition. The Arab Spring, home grown terrorism, geopolitical conflict, nationalistic politics and amebic ideological groups such as ISIS have fueled interest in American Muslims. This phenomenological qualitative study explored the lived experiences of Iraqi American Muslim immigrants as it relates to perceived employment discrimination. The study also explored whether or not such perceptions of employment discrimination impacted Detroit area American Muslims motivation to apply to future employment opportunities. The results of the exploratory research indicate that nearly half of Iraqi American Muslims felt that discrimination increased negative perceptions reduced their likelihood of applying to similar open positions in the future.